1962
DOI: 10.1182/blood.v19.6.702.702
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Stem Cells in the Peripheral Blood of Mice

Abstract: Leukocytes from the peripheral blood of normal F1 hybrid mice have been successfully used to promote survival of lethally irradiated parent and closely related homologous animals. Identification of donor-type red cells and leukocytes has been established on samples of blood taken from several long-term survivors. Histologic data and serologic typing of cells from lymph nodes, bone marrow, and spleens of chimeras killed early after irradiation and treatment established that injected peripheral leukocytes had tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
7

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(81 citation statements)
references
References 13 publications
0
74
0
7
Order By: Relevance
“…5,6 Mononuclear hematopoietic progenitor cells are present at low concentrations in the peripheral blood of a variety of species. [7][8][9] Development of techniques to both increase peripheral blood mononuclear cell (PBMC) counts using cloned hematopoietic cytokines 10,11 and collect large numbers of these cells via centrifugation using continuous-flow blood separators increased yields. [12][13][14] In dogs, both autologous 15,16 and allogeneic 17 PBMC grafts were able to reconstitute normal hematopoiesis after lethal bone marrow ablation.…”
mentioning
confidence: 99%
“…5,6 Mononuclear hematopoietic progenitor cells are present at low concentrations in the peripheral blood of a variety of species. [7][8][9] Development of techniques to both increase peripheral blood mononuclear cell (PBMC) counts using cloned hematopoietic cytokines 10,11 and collect large numbers of these cells via centrifugation using continuous-flow blood separators increased yields. [12][13][14] In dogs, both autologous 15,16 and allogeneic 17 PBMC grafts were able to reconstitute normal hematopoiesis after lethal bone marrow ablation.…”
mentioning
confidence: 99%
“…Early studies demonstrated that, in the physiological state, hematopoietic stem cells and their committed progenitors were present at low concentrations in the peripheral blood of mice, dogs, baboons, and humans. [49][50][51][52] However, large-scale use of PBMC grafts in human patients with life-threatening hematologic disorders awaited development of techniques to collect large numbers of PBMCs and preclinical validation of PBMC grafting protocols. Leukaphereses have been reported in dogs since 1967 for the purpose of transplanting circulating hematopoietic stem cells and for evaluating granulocyte therapeutic support.…”
mentioning
confidence: 99%
“…HSCs have long been known to be present in peripheral blood; this is most directly demonstrated by the long-term multilineage reconstitution observed in recipients of transferred whole blood. [40][41][42][43] HSCs are not the sole progenitor in the circulation, as more downstream MPPs and LMPPs can be reliably detected in blood as well, though at very low frequencies. 36,38,43 Relatively little is known about the physiologic mechanisms that govern the egress of BM progenitors into the blood.…”
Section: Mobilization Of Bm Progenitors Into Bloodmentioning
confidence: 99%